ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS VIII PADA POKOK BAHASAN HIMPUNAN - Rismawati, Melinda; Isa, Rupinus; Rindiani, Anita B (Department of Mathematics Education , University of Jember, 2022)
The purpose of this study was to determine the students' mathematical problem solving ability in completing the set material. The set is one of the junior high school mathematics subject matter in class VIII. The sample selection was done by purposive sampling and obtained as many as 24 students from class VIII. Data collection was carried out using a test instrument where the researcher was the main instrument and a problem-solving ability test in the form of 4 essay questions with 4 Polya indicators and interviews as a supporting instrument. The data processing technique used is to assess the results of students' answers based on indicators of problem solving abilities. The results of this study indicate that the 4 test questions given, there are still some errors found in the results of student answers in solving problem solving problems, such as: not providing the completion process, lack of understanding of the problem, errors in calculations, and incorrect conclusions due to calculation errors